Paraskevas Matalas, Κοσμοπολίτες εθνικιστές: Ο Μωρίς Μπαρές και οι ανά τον κόσμο “μαθητές”του [Cosmopolitan nationalists: Maurice Barres and his “disciples” around the world] - Karafoulidou, Vicky (The Historical Review/La Revue Historique, 2023)
Review of Paraskevas Matalas, Κοσμοπολίτες εθνικιστές: Ο Μωρίς Μπαρές και οι ανά τον κόσμο“μαθητές”του [Cosmopolitan nationalists: Maurice Barres and his “disciples” around the world]